Institutional Belonging and Social Self-Efficacy as Predictors of Perceived Ostracism Among Preservice Teachers - Anastasia Vatou; Maria Evangelou-Tsitiridou; Evridiki Zachopoulou; Vasilis Grammatikopoulos (Education Sciences)
The teaching profession is consistently ranked as one of the most stressful occupations worldwide, creating an urgent need for teacher education programmes to prepare highly skilled and reliant educators. Rooted in social cognitive theory, this study aims to explore preservice teachers’ social self-efficacy beliefs and examine its associations with institutional belonging and perceived ostracism. Social self-efficacy describes one’s confidence in one’s ability to engage in interpersonal relationships, and institutional belonging reflects the extent to which one feels valued and accepted within an institution, while ostracism reflects one’s experience of social exclusion. Two hundred and seventy-one preservice teachers from Greece were recruited to participate in this study via convenience sampling. The measures used were the Perceived Social Self-Efficacy scale (PSSE), Institutional Belongness questionnaire (IB), and Workplace Ostracism Scale (WOS). The results of descriptive statistics showed that preservice teachers’ levels of sense of belonging and social self-efficacy were moderate to high, while they experienced low levels of perceived ostracism. The results of regression analyses indicated that institutional belonging positively correlated with social self-efficacy and negatively with perceived ostracism. The mediation analysis results demonstrated that social self-efficacy partially mediates the relationship between institutional belonging and perceived ostracism. Collectively, the findings highlight the importance of developing a supportive educational environment that promotes both a sense of belonging and efficacy beliefs. Enhancing these factors could support preservice teachers’ wellbeing and commitment to the profession and inform policies and practices that promote inclusive educational environments.